The Mediating Role of Organizational Culture in the Relationship Between Leadership Styles and Employee Engagement: An Analytical Study of Kurdistan Manufacturing Companies - Hazhar Omer Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The study’s major aim is to explore and analyze the mediation role of organizational culture between leadership styles and employee engagement within Kurdistan manufacturing companies. As a result, a structural equation model was estimated using 140 questionnaire responses collected from a cluster of 35 selected manufacturing companies in Erbil, Kurdistan. The collected data was analysed using a structural equation modelling approach with the aid of Smart PLS data analysis program. The results of the study demonstrated that organizational culture lowly and significantly mediate the relationship between transformational leadership and employee engagement, and moderately and significantly mediate the relationships between supportive leadership and employee engagement. It was further revealed that organizational culture does not mediate the relationships between empowering leadership and employee engagement. The study recommends manufacturing companies to consider implementing multifaceted strategies that address both leadership development and the cultivation of a conducive organizational culture.